A genetic linkage map of water yam (Dioscorea alata L.) based on AFLP markers and QTL analysis for anthracnose resistance - Mignouna, Hodeba D.; Mank, R.A.; Ellis, T.H.N.; Bosch, N.V.D.; Asiedu, Robert; Abang, Mathew M.; Peleman, J. (Springer, 2002)
A genetic linkage map of the tetraploid water yam (Dioscorea alata L.) genome was constructed based on 469 co-dominantly scored amplified fragment length polymorphism (AFLP) markers segregating in an intraspecific F1 cross. The F1 was obtained by crossing two improved breeding lines, TDa 95/00328 as female parent and TDa 87/01091 as male parent. Since the mapping population was an F1 cross between presumed heterozygous parents, marker segregation data from both parents were initially split into maternal and paternal data sets, and separate genetic linkage maps were constructed. Later, data analysis showed that this was not necessary and thus the combined markers from both parents were used to construct a genetic linkage map. The 469 markers were mapped on 20 linkage groups with a total map length of 1,233 cM and a mean marker spacing of 2.62 cM. The markers segregated like a diploid cross-pollinator population suggesting that the water yam genome is allo-tetraploid (2n = 4x = 40). QTL mapping revealed one AFLP marker E-14/M52-307 located on linkage group 2 that was associated with anthracnose resistance, explaining 10% of the total phenotypic variance. This map covers 65% of the yam genome and is the first linkage map reported for D. alata. The map provides a tool for further genetic analysis of traits of agronomic importance and for using marker-assisted selection in D. alata breeding programmes. QTL mapping opens new avenues for accumulating anthracnose resistance genes in preferred D. alata cultivars.